2013
DOI: 10.2478/raon-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute/late toxicity and local recurrence in Τ1-Τ2 glottic carcinoma treated with accelerated hypofractionated 3D-conformal external beam radiotherapy (3D-CRT)

Abstract: BackgroundThe aim of the study was to evaluate the efficacy, as well as the acute and late toxicity of an accelerated hypofractionated 3DCRT schedule as radical treatment in patients with organ confined glottic cancer cT1-2N0.Patients and methods.Between June of 2004 and September 2010, 47 retrospectively selected patients (29 males, 18 females) diagnosed with organ confined T1 or T2 glottic cancer, were treated with external 3DCRT in an accelerated hypofractionation schedule. The median age was 70 years. A do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…However, one of the continuing challenges in the therapeutic approach towards laryngeal squamous cell carcinoma (LSCC) is the development of resistance to chemotherapy and radiation treatment [ 3 , 4 , 5 ]. Although X-ray dose escalation techniques have been used to counteract radioresistance, dose escalations to 64.4 Gy in T1–T2 glottic carcinoma yield significant acute and late toxicities [ 6 ]. As a result, a significant number of researches have aimed at the identification of novel agents capable of overcoming these adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the continuing challenges in the therapeutic approach towards laryngeal squamous cell carcinoma (LSCC) is the development of resistance to chemotherapy and radiation treatment [ 3 , 4 , 5 ]. Although X-ray dose escalation techniques have been used to counteract radioresistance, dose escalations to 64.4 Gy in T1–T2 glottic carcinoma yield significant acute and late toxicities [ 6 ]. As a result, a significant number of researches have aimed at the identification of novel agents capable of overcoming these adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…No difference in toxicity between standard and hypofractionated protocols was found in published reports of hypofractionated RT of the laryngeal cancer. 11,13,18,22,23,25 In majority of these reports a fraction dose of 2.25-2.5 Gy was used. The dose >3.0 Gy was linked to a higher complications rate, 13,34 but in a group of 200 patients reported by Gowda et al in which 3.12-3.28 Gy doses were used for 3 weeks up to a total of 50-52.5 Gy, early and late toxicity were low.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been proposed by other authors. 11,35 In published reports number of patients treated with hypofractionated RT was limited and authors suggested a need for further research. 10,12,18,35 The group with hypofractionated RT reported in this paper is one of the largest published so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation